AN EMPIRICAL TEST OF SOCIAL INFORMATION PROCESSING THEORY AND EMOTIONS IN VIOLENT SITUATIONS - K. N. Bowen; J. J. Roberts; E. Kocian; A. Bartula (Russian Journal of Economics and Law)
Objective: to study the decision-making process in high-risk-for-violence situations.Methods: formal-legal, sociological, method of hierarchical generalized linear modeling.Results: criminological research has favored the rational choice perspective in studying offender decision making. However, this theoretical approach does not take into account the complex interplay of situational, cognitive, emotional, and person factors that likely influence criminal decision making. To that end, the current study examines decision making in high-risk-for-violence situations focusing on social information processing and emotional state variables. The current study utilizes a sample of 236 newly incarcerated jailed inmates who provide personal level data and situational reports of violent and avoided violence situations (n = 466).Scientific novelty: the findings for the first time show that several situational, social information processing, and emotion variables, such as intent interpretation, goal, and response generation, are significant predictors of the escalation of violence, hence increasing the probability of committing a crime.Practical significance: the main provisions and conclusions of the article can be used in scientific and law-enforcement activities when considering the issues of identifying and eliminating the reasons and conditions of crime committing, as well as with influencing the individuals in order to prevent crimes or anti-social behavior.